If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(6x + 10) = 280 Reorder the terms: 7(10 + 6x) = 280 (10 * 7 + 6x * 7) = 280 (70 + 42x) = 280 Solving 70 + 42x = 280 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-70' to each side of the equation. 70 + -70 + 42x = 280 + -70 Combine like terms: 70 + -70 = 0 0 + 42x = 280 + -70 42x = 280 + -70 Combine like terms: 280 + -70 = 210 42x = 210 Divide each side by '42'. x = 5 Simplifying x = 5
| 9a^2(-5a^3+5a-5)= | | 4-8a=4(1-2a) | | 4sin^2(x)=2 | | 3g+5=7b-7.4 | | .35x+.30x=22.75 | | 8(n+6)+8=7n | | .35x+.30x=2275 | | -20=5x+5x+10 | | 9z=40500 | | -x-4=7x-68 | | (3p-7)=(5p-6) | | 10-6x+3x=-2 | | 29=76-46 | | 2(n+2)=5-5n | | 720=12x+100 | | -3n^5(5n+4)= | | 5m+6+4(3m-5)-5(m+5)=0 | | 7x+-4=1x+32 | | 12n+2(n-3)=1+5(2n-1) | | 12x+11y=18 | | 4b+3-b=4(b-5)+2 | | 0.4(p+1)-0.9(p+5)=-2 | | (2x^2+3x-6)-(x^2-18x+6)= | | -250+5(5)= | | 6(7x+9)=264 | | 6(3+k)=48 | | c-(-75)=25 | | -250+5(3)= | | 4(h+8)=16 | | 6-4u=2 | | a(6a^2+2a+9)= | | 6(2-x)=20 |